Konflik Elit Lokal Dalam Pemilihan Kepala Daerah Maluku Utara - RUSDI J ABBAS (Jurnal Studi Pemerintahan, 2011)
This research explains on local elite conflict that happened in the election of regional leader of NorthMaluku 2007-2008. This research uses inductive approach with literature and in-depth interview. Thearea of this research is Ternate City. The result of this research shows that local elite contentionhappened in some areas confronting them, either in small arenas or big arenas. The source of thisconflict was taken from province of North Maluku 1999 formation, behind of Abdul Gaffur and ThaibArmayin's elite local emulation and regional leader election of North Maluku 2001-2002. Otherwise,configuration of local elite existing in North Maluku is divided into three big parts. They weretraditional elite, new elite, and local elite. The Election of regional leader of North Maluku 2001-2002could be said as an arena contention of elite local of North Maluku which happened in big scale, in thisarena Abdul Gaffur who won the previous election, finally had to fail tragically and was removed byThaib Armayin.